Eco-friendly synthesis of azo Schiff base ligand and its metal complexes: Anticancer, antidiabetic and antimicrobial activities - Sakhare, Kuldeep B.; Sarwade, Kirti N.; Bharate, Yogesh N.; Sakhare, Mahadeo A (Mongolian Journal of Chemistry, 2025)
Now a days Cancer, Diabetics and other diseases are become major issue of the society. Due to this synthesis of potential medicines against it is a major challenge to the researcher and hence Schiff base ligand became an attracting class of researcher. The azo Schiff base ligands are most widely used in various fields such as medicinal, pharmacological, biological etc. due to its broad spectrum of biological activity. In this research paper we have synthesized the Azo-Schiff base ligand and its transition metal complexes by simple griding method. Synthesis via green approach and biological evolution of azo-Schiff base ligand and its Mn(II), Co(II), Ni(II), Cu(II), Zn(II) and VO(II) metal complexes. These compounds were characterized by Mass, 1H-NMR, FT-IR, Elemental analysis, Molar conductance, magnetic susceptibility, UV-Vis., P-XRD, TGA etc. and were screened for biological activities. Synthesised azo-Schiff base ligand and it’s metal complexes were evaluated for their antimicrobial, antidiabetic as well as anticancer activities against various bacteria and fungi, acarbose and MCF-7 breast cancer cell line respectively. From the findings of various results we can conclude that the synthesized metal complexes exhibit higher biological activities than that of azo-Schiff base ligand.